Towards the Humanisation of Birth A study of epidural analgesia and hospital birth culture - Newnham, Elizabeth (Springer International Publishing, 2018)
This book examines the future of birthing practices, particularly by focusing on epidural analgesia in childbirth. It describes historical and cultural trajectories that have shaped the way in which birth is understood in Western, developed nations. In setting out the nature of epidural history, knowledge and practice, the book delves into related birth practices within the hospital setting. By critically examining these practices, which are embedded in a scientific discourse that rationalises and relies upon technology use, the authors argue that epidural analgesia has been positioned as a safe technology in contemporary maternity culture, despite it carrying particular risks. In examining alternative research the book proposes that increasing epidural rates are not only due to greater pain relief requirements or access but are influenced by technocratic values and a fragmented maternity system. The authors outline the way in which this epidural discourse influences how information is presented to women and how this affects their choices around the use of pain relief in labour.